2012
DOI: 10.1108/17549451211285735
|View full text |Cite
|
Sign up to set email alerts
|

Realistic expectations with brain computer interfaces

Abstract: Purpose -This paper describes the research underpinning the development and evaluation of a brain computer interface (BCI) system designed to be suitable for domestic use by people with acquired brain injury in order to facilitate control of their home environment. The purpose of the research is to develop a robust and user-friendly BCI system which was customisable in terms of user ability, preferences and functionality. Specifically the human interface was designed to provide consistent visual metaphors in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…BCIs offer users various opportunities for social participation. One way is to include potential or actual BCI users in research and technology development processes [31][32][33]. Other studies have acknowledged the importance of social participation for users [21,24].…”
Section: "[…]mentioning
confidence: 99%
“…BCIs offer users various opportunities for social participation. One way is to include potential or actual BCI users in research and technology development processes [31][32][33]. Other studies have acknowledged the importance of social participation for users [21,24].…”
Section: "[…]mentioning
confidence: 99%
“…Additionally, Mulvenna et al [24] suggests personalizing the BCI system for individual needs to increase the lower efficacy rates by users with ABI while Schreuder and his team [23] felt that a range of cognitive profiles need to be taken into account at the design stage of BCI development. A number of biological, psychological and social factors could have impacted on the accuracy score that were not controlled for in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has explored BCI technology with acquired brain injury end-users [24]. It is recently been identified that some people with ALS can also experience cognitive impairments [25].…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…For example, to design a suitable BCI system for domestic use by people with acquired brain injury in order to facilitate control of their environment, Mulvenna et al (2012)  The interaction, e.g., do you prefer to imagine that your hand is moving or to focus in order to move the avatar? Which other interaction device can be used in addition to the BCI?…”
Section: Identification Methods Of Existing Needsmentioning
confidence: 99%